Theoretical Reflection about a Fuzzy Definition of the Rural. (Sociología y Tecnociencia, 2015)
The rurality definition is yet unclear. Pragmatic classifications are currently used for the management of rural and urban differentiation of this one. The aim of this article is to propose a definition of rurality. This one is based on the fuzzy sociological research. Our fuzzy concept of rurality is very important for its application on the management of the technoscientific system, specifically on the management of the rural.